Archaeological sites as Distributed Long-term Observing Networks of the Past (DONOP). (30th May 2020) - Hambrecht, George; Anderung, Cecilia; Brewington, Seth; Dugmore, Andrew; Edvardsson, Ragnar; Feeley, Francis; Gibbons, Kevin; Harrison, Ramona; Hicks, Megan; Jackson, Rowan; Ólafsdóttir, Guðbjörg Ásta; Rockman, Marcy; et al.
Abstract: Archaeological records provide a unique source of direct data on long-term human-environment interactions and samples of ecosystems affected by differing degrees of human impact. Distributed long-term datasets from archaeological sites provide a significant contribution to establish local, regional, and continental-scale environmental baselines and can be used to understand the implications of human decision-making and its impacts on the environment and the resources it provides for human use. Deeper temporal environmental baselines are essential for resource and environmental managers to restore biodiversity and build resilience in depleted ecosystems. Human actions are likely to have impacts that reorganize ecosystem structures by reducing diversity through processes such as niche construction. This makes data from archaeological sites key assets for the management of contemporary and future climate change scenarios because they combine information about human behavior, environmental baselines, and biological systems. Sites of this kind collectively form Distributed Long-term Observing Networks of the Past (DONOP), allowing human behavior and environmental impacts to be assessed over space and time. Behavioral perspectives are gained from direct evidence of human actions in response to environmental opportunities and change. Baseline perspectives are gained from data on species, landforms, and ecology over timescales that long predate our typically recent datasets that only record systems already disturbed by people. Biological perspectives can also provide essential data for modern managers wanting to understand and utilize past diversity (i.e., trophic and/or genetic) as a way of revealing, and potentially correcting, weaknesses in our contemporary wild and domestic animal populations.